Removal of Forearm Plate Leads to a Higher Risk of Refracture—A Systematic Review and Meta‐Analysis - Renwei Cao; Jianyu Zhang; Weitong Sun; Xieyuan Jiang; Kehan Hua; Dan Xiao; Chen Chen; Yejun Zha; Maoqi Gong (Orthopaedic Surgery)
ABSTRACT Objective Plate fixation is the preferred method for treating forearm shaft fractures. However, it remains controversial regarding the necessity of implant removal after bone union. This review aims to assess refracture risk after plate removal. Methods We searched various data sources, including PubMed, Embase, Web of Science, and Cochrane Library. A total of 6749 papers were identified, of which 23 studies were eligible for final quantitative syntheses. Subgroup analyses and sensitivity analyses were conducted to reduce heterogeneity and make the results more reliable. Results The total risk difference (RD) was 0.06 (0.04–0.09), indicating that the difference was significant. In the “Reasons for Removal” subgroup analysis, the RD of the “No Symptom” subgroup was 0.07 (95% CI = 0.04–0.11), while the RD of the “Symptoms” subgroup was 0.04 (95% CI = −0.02 to 0.10). In the “Plate Type” subgroup analysis, the RD of the “LCP” subgroup was 0.07 (95% CI = 0.02–0.13), while the RD of the “DCP” subgroup was 0.07 (95% CI = 0.01–0.13). After omitting each study one by one, the RDs were all significant. Conclusions Plate retention is significantly associated with a lower rate of refracture than plate removal. Consequently, it is not recommended to remove implants, especially for patients without implant‐related symptoms, but more reliable evidence is still needed. Trial Registration The review was registered on PROSPERO and the registration ID is CRD42023424743, and a protocol was not prepared